Respon Pertumbuhan Bibit Tembakau (Nicotiana Tabacum L.) Dengan Pengaplikasian Limbah Solid Pada Media Tanam - Irfan Kusnadi; Rizki Nia Sukri Nasution; Azri Gilang Ramdhan Daulay (HORIZON: Indonesian Journal of Multidisciplinary, 2023)
Tobacco seeding can be done in several ways, namely conventionally and polybags or with the use of seed-trays. This study was conducted with the aim of knowing the effect of solid waste on planting media on the growth of tobacco seedlings. To determine the effect of solid waste on the best growing media on the growth of tobacco seedlings. This study used a completely randomised design (CRD) with 4 treatments and 6 replications. With the following treatments: S0 = Topsoil 100%, S1 = Top soil 75% and Solid 25% S2 = Top soil 50% and Solid 50% S3 = Top soil 25% and Solid 75%. The data obtained were analysed with F test. LSD (Least Significant Difference) test at the α = 5% level. The results showed that the treatment of the composition of solid waste in the growing media on the growth of tobacco seedlings had a significant effect on the growth of tobacco seedlings, namely in the parameters of seedling height, number of leaves, stem diameter, leaf length, leaf width. The treatment of the composition of planting media top soil 25% and solid 75% is the best treatment in the growth of tobacco seedlings.